The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.26848/rbgf.v12.5.p1844-1852
|View full text |Cite
|
Sign up to set email alerts
|

Estudo De Caso De Contribuição Do Fluxo De Umidade Em Evento De Precipitação Intensa Ocorrido No Leste Do Nordeste Do Brasil Em Maio De 2017

Abstract: A observação de distribuição espacial e temporal do regime de chuvas da região Nordeste do Brasil (NEB) torna-se um desafio devido sua grande variabilidade no tempo e no espaço. Durante o período de 25 a 29 de maio de 2017 foram registrados casos de chuvas intensas na parte leste do NEB, principalmente entre os estados de Alagoas e de Pernambuco. Desta forma, objetivo deste trabalho consistiu em verificar a contribuição do fluxo de umidade associada ao evento de precipitação severa ocorrido na região leste do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Researchers analyzed the moisture flux of precipitation system events on the NEB east coast and observed that the region is characterized by the convergence of humidity borne by the trade winds, east waves and breezes associated with the topography, in addition to the circulation and the transport of moisture from the ocean towards the continent, where it contributes to feeding the convection over the surface. This caused the occurrence of landslides in the respective regions of those studies [31,32].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Researchers analyzed the moisture flux of precipitation system events on the NEB east coast and observed that the region is characterized by the convergence of humidity borne by the trade winds, east waves and breezes associated with the topography, in addition to the circulation and the transport of moisture from the ocean towards the continent, where it contributes to feeding the convection over the surface. This caused the occurrence of landslides in the respective regions of those studies [31,32].…”
Section: Resultsmentioning
confidence: 95%
“…the transport of moisture from the ocean towards the continent, where it contributes to feeding the convection over the surface. This caused the occurrence of landslides in the respective regions of those studies [31,32].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation